DNA microarrays : a molecular cloning manual - Bowtell, David; Sambrook, Joseph (Cold Spring Harbor Laboratory Press, 2003)
DNA microarray, or DNA chip, technology is a new and powerful means of discovering, characterizing, and analyzing genes and their expression patterns. The potential of this technology is huge and its applications are widespread across the many fields of biological and biomedical research. This manual assembles and synthesizes the expertise of over 30 innovators in this emerging field to provide authoritative, detailed instruction on the design, construction, and applications of microarrays, as well as comprehensive descriptions of the software tools and strategies required for extensive image and data analysis. Designed to extend and to complement the information in the best-selling laboratory manual Molecular Cloning, and presented in the same clear, user-friendly format, this book is an essential resource for investigators studying the molecular profiles of gene expression in any experimental system.
Keywords: biologie; Reference Books; DNA; klonování DNA; biomedicínské inženýrství; Cloning, Molecular; referenční knihy